Shedding light on the free radical nature of sulfonated melanins - Batagin-Neto, A. [UNESP]; Mostert, A. B.; Paulin, J. V. [UNESP]; Meredith, P.; Graeff, C. F.O. [UNESP] (American Chemical Society (ACS), 2020)
Melanin, an important class of natural pigment found in the human body, has stood out as a promising bioelectronic material due to its rather unique collection of electrical properties and biocompatibility. Among the available melanin derivatives, the sulfonated form has proven to not only be able to produce homogeneous device quality thin films with excellent adhesion, even on hydrophobic surfaces, but also to act as an ion to electron transducing element. It has recently been shown that the transport physics (and dominant carrier generation) may be related to a semiquinone free radical species in these materials. Hence, a better understanding of the paramagnetic properties of sulfonated derivatives could shed light on their charge transport behavior and thus enable improvement in regard to use in bioelectronics. Motivated by this question, in this work, different sulfonated melanin derivatives were investigated by hydration-controlled, continuous-wave X-band electron paramagnetic resonance spectroscopy and electronic structure calculations. Our results show that sulfonated melanin behaves similarly to non-functionalized melanin, but demonstrates a less pronounced response to humidity vis-a-vis standard melanin. We thus speculate on the structural and charge transport behavior in light of these differences with a view to further engineering structure−property relationships.